Palynology of six middle and late Holocene peat sections, Baffin Island - Short, Susan; Andrews, John (Géographie physique et Quaternaire, 1980)
Palynological investigations were undertaken at six sites on the northern Cumberland Peninsula, Baffin Island. Pollen assemblages from the Canadian High Arctic are rare, and the purpose of this paper is to expand this record. Twelve pollen diagrams from the six sites are presented. They suggest that over the last 1000 years, the pollen rain has been dominated by pollen of the gra-minoid group. This contrasts with earlier pollen assemblages between 2500 and 2000 years BP and between 5000 and 4000 BP which were typically more diverse and included significant quantities of heath and shrub (willow) pollen. A pronounced willow peak is evident on the diagrams and dates from ca. 2500 BP.